Analysis of hydrodynamic interference between two foils using a boundary element method. (1st March 2020) - Hu, Jian; Liu, Lichao; Guo, Chunyu; Sun, Shili
Abstract: A potential-based boundary element method for the hydrodynamic analysis of a two-dimensional (2-D) steady surface flow passing over two foils is described. A vortex sheet is placed within each foil to produce the desired circulations. The total potential is decomposed into three parts consisting of the potential of the incoming flow, the disturbed potential from sources, and the disturbed potential caused by the vortex sheets. The boundary integral equation and two complementary equations derived from the Kutta condition at the trailing edge of each foil are placed in the same numerical matrix and solved together to obtain the potential on the foil, as well as the vortex strengths. Extensive convergence studies are then performed. The interactions between the foils are then discussed. The free surface effect on the hydrodynamics are quantitatively reported. The numerical results showed that the free surface greatly affected the lift and drag of the foils, and at a proper relative location, the wave excitation was diminished due to the interaction between the foils.